The effect of titanium oxide and hydroxyapatite on the mechanical properties of wollastonite - D. Ragurajan; M. Satgunam; M. Golieskardi; U. Sankar; Angela Min Hwei Ng (Cogent Engineering, 2019)
The effect of incorporation of titanium oxide (TiO2) and hydroxyapatite (HA) on the mechanical properties of wollastonite (CaSiO3) was investigated in this study. TiO2/CaSiO3/HA composites were prepared and characterized by means of physical and mechanical properties. Morphology analysis revealed that the wollastonite composite possesses a rough surface. Moreover, the addition of TiO2 and HA to wollastonite was evaluated by means of bulk density and Vickers Hardness. The wollastonite composites containing TiO2 (10–30 wt%) and HA (20–40 wt%) were sintered between 1230°C and 1270°C, with a ramp rate of 10°C/min and a holding time of 2 h. The results indicated that the additives played a significant part in enhancing the physical and mechanical properties of the composite wollastonite in comparison to the pure wollastonite, particularly in composites containing higher percentage of TiO2 (25–30 wt%) and lower HA (20–25 wt%). Furthermore, the results obtained from the XRD analysis revealed that the newly formed apatite particles on the surface of the wollastonite composite were comprise of superfine crystalline and/or defective structure grains.